PERENCANAAN PENGELOLAAN SAMPAH DI JALUR PENDAKIAN TAMAN NASIONAL GUNUNG RINJANI - Maiser Syaputra (Forestry Study Program University Of Mataram, 2019)
There is four hiking track in the Gunung Rinjani National Park area, namely Senaru, Sembalun, Timbanuh, and Aik Berik. In 2016 there were 93,018 visitors to Mount Rinjani National Park. A large number of a visitor can be a potential because it contributes to state revenues, but on the other side, the presence of waste become manager's homework because the higher number of visitor occurs waste also getting bigger. This study aim is to develop a waste management plan in the hiking track of Mount Rinjani National Park.